2011
DOI: 10.1074/jbc.m110.211284
|View full text |Cite
|
Sign up to set email alerts
|

Residues 155 and 348 Contribute to the Determination of P2X7 Receptor Function via Distinct Mechanisms Revealed by Single-nucleotide Polymorphisms

Abstract: P2X 7 receptors are important in mediating the physiological functions of extracellular ATP, and altered receptor expression and function have a causative role in the disease pathogenesis. Here, we investigated the mechanisms determining the P2X 7 receptor function by following two human single-nucleotide polymorphism (SNP) mutations that replace His-155 and Ala-348 in the human (h) P2X 7 receptor with the corresponding residues, Tyr-155 and Thr-348, in the rat (r) P2X 7 receptor. H155Y and A348T mutations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
66
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(78 citation statements)
references
References 83 publications
11
66
1
Order By: Relevance
“…While conflicting results are present in the literature for this specific SNP, our data are consistent with [23,27] showing that the 348Thr variant also generates a gain of function phenotype.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…While conflicting results are present in the literature for this specific SNP, our data are consistent with [23,27] showing that the 348Thr variant also generates a gain of function phenotype.…”
Section: Resultssupporting
confidence: 90%
“…However, significant differences in maximum responses were identified for both modes of activation (178 ± 6% and 126 ± 12% for pore and channel function, respectively, Table  1), confirming previous findings of a GOF phenotype driven by 155Tyr [22,23,25-27]. …”
Section: Resultssupporting
confidence: 88%
“…The underlying mechanisms behind these gain-of-function effects have not been established. There is some evidence to suggest that the amino acid variation at 155 increases cell surface expression of P2X7 (Bradley et al, 2011a); however, this was not observed in the initial report of this SNP (Cabrini et al, 2005). One of the most interesting SNPs in human P2RX7 is Q460R in the C terminus.…”
Section: A P2x7 Single Nucleotide Polymorphismsmentioning
confidence: 54%
“…Roger et al mapped single nucleotide polymorphisms identified in affective mode disorders on to the model, and were able to suggest mechanisms by which the mutations caused impairment in channel function [112]. This model was also used in a further study analysing two gain-of-function SNPs in human P2X7 (H155Y and A348T), comparing them with their reciprocal mutations in rat P2X7 [113]. Finally, the same model was used in a paper comparing the function of the highly homologous human and rhesus macaque P2X7…”
Section: P2x7mentioning
confidence: 99%